2017
DOI: 10.4103/0366-6999.205862
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Current Interventions in Shock Patients in Chinese Emergency Departments

Abstract: Background:Shock is a life-threatening condition in emergency departments (EDs) and is associated with a high mortality; however, its clinical characteristics and current interventions in China are seldom reported. This study investigated the clinical characteristics and current interventions of shock patients in Chinese EDs.Methods:This multicenter prospective cohort study was conducted in the EDs of 33 academic hospitals in 16 Chinese provinces. Adult shock patients were enrolled from December 2013 to April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Aggregating data reported in 14 published cohorts and two unpublished data-sets, Leopold et al [21] reported that epinephrine use was associated with an increased risk of death in patients with cardiogenic shock. In a cohort of 168 patients with cardiogenic shock, norepinephrine was associated with a lower risk of death compared to patients receiving epinephrine or dopamine [22].…”
Section: Vasopressor Agentsmentioning
confidence: 94%
“…Aggregating data reported in 14 published cohorts and two unpublished data-sets, Leopold et al [21] reported that epinephrine use was associated with an increased risk of death in patients with cardiogenic shock. In a cohort of 168 patients with cardiogenic shock, norepinephrine was associated with a lower risk of death compared to patients receiving epinephrine or dopamine [22].…”
Section: Vasopressor Agentsmentioning
confidence: 94%
“…36 Epinephrine results in an increased likelihood of death even in observational studies. 56,59,62 Therefore, epinephrine is not recommended as a first-line agent for CS. 2 This drug still has a pivotal role in cardiac arrest, being associated with a significantly higher rate of 30-day survival versus placebo among patients with out-of-hospital cardiac arrest enrolled in the PARAMEDIC2 (Prehospital Assessment of the Role of Adrenaline: Measuring the Effectiveness of Drug Administration in Cardiac Arrest) trial, although severe neurologic impairment at hospital discharge was more frequent in the epinephrine group in such trial.…”
Section: Epinephrinementioning
confidence: 99%
“…An important contribution to the clinical use of epinephrine in CS comes from the already mentioned OptimaCC trial, where epinephrine was associated with a higher incidence of refractory shock as compared to norepinephrine 36 . Epinephrine results in an increased likelihood of death even in observational studies 56,59,62 . Therefore, epinephrine is not recommended as a first‐line agent for CS 2 .…”
Section: Overview Of Inotropic Therapiesmentioning
confidence: 99%
“…Shock is a life-threatening condition that can result in death (Guo et al, 2017) . There are various cases of shock that occur in both trauma and non-traumatic cases, including hypovolemic shock, cardiogenic shock, obstructive shock and distributive shock (Standl et al, 2018).…”
Section: Introductionmentioning
confidence: 99%